Vascular Signal Transducer and Activator of Transcription-3 Promotes Angiogenesis and Neuroplasticity Long-Term After Stroke. Issue 20 (19th May 2015) - Hoffmann, Christian J.; Harms, Ulrike; Rex, Andre; Szulzewsky, Frank; Wolf, Susanne A.; Grittner, Ulrike; Lättig-Tünnemann, Gisela; Sendtner, Michael; Kettenmann, Helmut; Dirnagl, Ulrich; Endres, Matthias; Harms, Christoph
<x xml:space="preserve">Abstract</x> Background— Poststroke angiogenesis contributes to long-term recovery after stroke. Signal transducer and activator of transcription-3 (Stat3) is a key regulator for various inflammatory signals and angiogenesis. It was the aim of this study to determine its function in poststroke outcome. Methods and Results— We generated a tamoxifen-inducible and endothelial-specific Stat3 knockout mouse model by crossbreeding Stat3floxed/KO and Tie2-CreERT2 mice. Cerebral ischemia was induced by 30 minutes of middle cerebral artery occlusion. We demonstrated that endothelial Stat3 ablation did not alter lesion size 2 days after ischemia but did worsen functional outcome at 14 days and increase lesion size at 28 days. At this late time point vascular Stat3 expression and phosphorylation were still increased in wild-type mice. Gene array analysis of a CD31-enriched cell population of the neurovascular niche showed that endothelial Stat3 ablation led to a shift toward an antiangiogenic and axon growth-inhibiting micromilieu after stroke, with an increased expression of Adamts9. Remodeling and glycosylation of the extracellular matrix and microglia proliferation were increased, whereas angiogenesis was reduced. Conclusions— Endothelial Stat3 regulates angiogenesis, axon growth, and extracellular matrix remodeling and is essential for long-term recovery after stroke. It might serve as a potent target for stroke treatment after the acute phase by fostering angiogenesis and neuroregeneration.